African values and institutional reform for sustainable development in Africa - Gabriel Asuquo (Center for Humanities and Innovation Studies, 2019)
The way society patterned its institutions and framed its laws, is predicated on the prevalent values of the people, which is rooted in their culture, philosophies, and spirituality. The way such a society makes progress and promotes coexistence is linked to the values that they uphold. Similarly, African values are those axiological principles that form the foundation of social living and social ordering in traditional African society, which can still be relevant today. These social values of the African people are what were used to construct African inclusive institutions in the traditional setting before it was eroded by colonialism and imperialism. Thus, for Africans of today to rebuild inclusive institutions that will guarantee sustainable development across the continent, there is a need to revive and reintegrate the principles from the study of African values into the reform of contemporary African social institutions. Therefore, in this paper, the authors argue that for African institutions to deliver the good of sustainable development, they must be reformed along the lines of foundational principles of African cultural values. The paper employs the philosophical method of critical analysis in dissecting the issues within this discourse.